Analysing influence of shareholder decision on green innovation knowledge sharing by fuzzy set qualitative comparative analysis combined evolutionary game theory - Wang, Zhenqing; Yang, Yuqi (Frontiers in Energy Research, 2023)
This article is based on the mixed ownership reform, with energy enterprises as the research object, and constructs a fuzzy set qualitative comparative analysis game framework for path optimization in complex systems. Using fsQCA and game theory from the perspective of knowledge sharing, reasonable assumptions are made for the sharing of green innovation knowledge between state-owned and non-state-owned shareholders in energy enterprises, providing policy support and institutional guarantee for the sharing of similar green innovation knowledge in multiple industries, to some extent, it facilitates the exchange and flow of green innovation knowledge among different enterprises, providing the optimal path for complex systems. This article can draw the following conclusions: 1. Government led, government enterprise driven, and enterprise led are the three major influencing paths for promoting green innovation knowledge sharing. The final trend of stable gaming among different types of shareholders depends on sharing profits. 3. The fuzzy set qualitative comparative analysis game framework has certain universality.